Regional increases in brain signal variability are associated with pain intensity reductions following repeated eccentric exercise bouts. (7th February 2020) - Boissoneault, Jeff; Sevel, Landrew; Stennett, Bethany; Alappattu, Meryl; Bishop, Mark; Robinson, Michael
Abstract: Background: Traditional pain interventions limit fluctuations in pain sensation, which may paradoxically impair endogenous pain modulatory systems (EPMS). However, controlled exposures to clinically relevant pain (e.g. delayed onset muscle soreness [DOMS]) may build capacity in the EPMS. Emerging evidence suggests that regional signal variability (RSV) may be an important indicator of efficiency and modulatory capacity within brain regions. This study sought to determine the role of RSV in both susceptibility to and trainability of pain response following repeated DOMS inductions. Methods: Baseline and follow‐up resting‐state fMRI was performed on 12 healthy volunteers 40 days apart. Between scanning visits, participants received four weekly DOMS inductions in alternating elbow flexors and were supplied seven days of post‐induction pain ratings. Voxel‐wise standard deviation of signal intensity was calculated to measure RSV. Associations among DOMS‐related pain and RSV were assessed with regression. Relationships among baseline and change measurements were probed (i.e. susceptibility to DOMS; trainability following multiple inductions). Results: Significant association between baseline RSV in left middle frontal gyrus (MFG) and right cerebellum and reductions in DOMS‐related pain unpleasantness were detected. Furthermore, increases in RSV were associated with reduced DOMS pain intensity (left lingual gyrus, right MTG, left MTG, left precuneus) and unpleasantness (left MTG, right SFG). Discussion: Findings suggest that RSV may be an indicator of EPMS resilience and responsivity to training, as well as an indicator that is responsive to training. Involved regions underlie cognitive, affective and representation processes. Results further clarify the potential role of RSV as an indicator of pain modulation and resilience. Significance: Regional signal variability may be an important indicator of endogenous pain modulatory system responsivity to training following repeated bouts of clinically relevant pain and may in fact be responsive to training itself.